Pengaruh Struktur Kepemilikan Institusional, Profitabilitas, Dan Resiko Perusahaan Terhadap Kinerja Intellectual Capital - Ade Apriliani; Henri Agustin; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to determine the effect of institusional ownwership structure, profitability, and company risk. the population in this study were all banking company registered at BEI from 2015-2018. The sample in this study is a total sampling technique, where the entri population is sampled. With a total sample 168 sample using a purposive sampling method. The results of empirical studies show that institutional ownership structure, risk do not affect IC has a positive effect on IC and profitability has a positive effect on IC. Recommendations for further research are expected to conduct research in different business fields such as manufacturing sector companies, real estate companies etc. Adding variables not examined in this study. With company size variables, leverge and other ownership structures.